A Comparison between the Effect of Education of Fetal Movement Counting during the Second and Third Trimesters on Maternal Fetal Attachment in First Time Pregnant Women - K Salehi; Z Salehi; Z Sohrabi (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: Maternal-Fetal Attachment (MFA) is one of the most important components in achieving motherhood identity. One of the recommended interventions in this regard is to consider fetal movement. Therefore, the present study evaluated the effect of education of fetal movement counting during the second and the third trimesters of pregnancy on MFA in first-time pregnant women. Materials & Methods: In this semi-experimental study, 47 pregnant mothers were selected through simple sampling from selected health-care centers in 2015.  Then, they were randomly allocated into two groups. Face-to-face training was provided on counting and recording the daily fetal movement. Next, the subjects in the first group counted and recorded the fetal movement in specific forms between the 24th and 28th weeks of pregnancy once a day and the second group did it between 28th and 32nd weeks. Before and after the intervention, both groups completed Cranley's Maternal-Fetal Attachment Scale. Data analysis was conducted, using SPSS 16, with a significance level of p < 0.05. Paired t-test was used to compare the mean score of MFA before and after the intervention in each group and independent t-test was used for between groups comparison. Results: The mean score of MFA before the intervention in the first group was 86.63 ± 11.62 and in the second group was 90.50 ± 8.93. No significant difference was observed between the two groups. After the intervention, the mean score of MFA was 96.30 ± 10.81 in the first group and 95.92 ± 11.40 in the second group. This change was statistically significant in both groups (first group: p = 0.001, second group: p = 0.01); but the changes of maternal-fetal attachment had no significant difference between the two groups. Conclusions: Education of fetal movement counting during the second and third trimesters had a similar effect on MFA. For more accurate evaluation of the effect of this intervention in different times, it is recommended to perform this study with a control group.